2020
DOI: 10.1021/acsnano.0c07262
|View full text |Cite
|
Sign up to set email alerts
|

Organogermanium Nanowire Cathodes for Efficient Lithium–Oxygen Batteries

Abstract: We report a technique for effectively neutralizing the generation of harmful superoxide species, the source of parasitic reactions, in lithium−oxygen batteries to generate stable substances. In organic electrolytes, organogermanium (Propa-germanium, Ge-132) nanowires can suppress solvated superoxide and induce strong surface-adsorption reaction due to their high anti-superoxide disproportionation activity. Resultantly, the effect of organogermanium nanowires mitigate toxic oxidative stress to stabilize organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Particularly, the adsorption energies on the side wall of the NW are less than those on the top of the NW and the substrate, indicating that the special configuration would ameliorate the characteristics of Ge anode effectively. 30–33 Compared with ordinary planar Ge model, the Ge NW model in this work has a larger specific surface area. Kohandehghan et al 19 experimentally demonstrated that Ge NW had higher capacity than planar germanium.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, the adsorption energies on the side wall of the NW are less than those on the top of the NW and the substrate, indicating that the special configuration would ameliorate the characteristics of Ge anode effectively. 30–33 Compared with ordinary planar Ge model, the Ge NW model in this work has a larger specific surface area. Kohandehghan et al 19 experimentally demonstrated that Ge NW had higher capacity than planar germanium.…”
Section: Resultsmentioning
confidence: 99%